Basin inversion: reactivated rift structures in the central Ligurian Sea revealed using ocean bottom seismometers - M. Thorwart (Copernicus Publications, 2021)
The northern margin of the Ligurian Basin shows notable seismicity at the Alpine front, including frequent magnitude 4 events. Seismicity decreases offshore towards the Basin centre and Corsica, revealing a diffuse distribution of low-magnitude earthquakes. We analyse data of the amphibious AlpArray seismic network with focus on the offshore component, the AlpArray ocean bottom seismometer (OBS) network, consisting of 24 broadband OBSs deployed for 8 months, to reveal the seismicity and depth distribution of micro-earthquakes beneath the Ligurian Sea.